Religious Dialectics In The Election Context As An Effort To Maintain Nation's Integrity - Rohman, Adi Nur (Law Research Review Quarterly, 2018)
Elections are a manifestation of democracy that aims to directly elect heads of state, regional heads or representatives in parliament. Unfortunately, the implementation of elections often leaves various conflicts that arise in the community. Among the various issues that emerged were religious issues which returned to be the main issue in the Democratic Party event as well as in this year's presidential election. Some people consider that religion is only used as a political commodity to fulfill the interests of a group while others see that it is part of the implementation of religious values. As a result, horizontal conflict because and in the name of religion re-emerged which resulted in the nation's divisions difficult to avoid. Throwing issues and information involving religious elements to legitimize personal interests and groups became commonplace both online and offline with their respective approaches. This paper attempts to reconstruct the conception of religion in applying religious values ​​and teachings in the context of elections in Indonesia. Ethics, legal norms and religious norms should be used as references by not ignoring the principles of fair and fair elections. Religious dialectics through the embodiment of religious values ​​and teachings is truly an important instrument in the democratic process in Indonesia. In the end, the concept of democracy which has a faith accompanied by religious values ​​will be able to build and maintain the integrity of the nation in the framework of the Pancasila.